2013
DOI: 10.7705/biomedica.v33i4.1536
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la calidad metodológica de la literatura en evaluación económica en salud en Colombia: una revisión sistemática

Abstract: Introducción. La evaluación económica es una herramienta que contribuye a establecer prioridades en la toma de decisiones en salud. La calidad metodológica de los estudios realizados en Colombia no se ha evaluado de manera sistemática. Objetivo. Valorar la calidad metodológica de las evaluaciones económicas en salud publicadas en Colombia. Materiales y métodos. Se llevó a cabo una revisión sistemática de evaluaciones económicas completas (costos y efectividad de, al menos, dos programas o servicios de salud) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
3
8
0
2
Order By: Relevance
“…As reported in earlier systematic reviews of HEE studies in Latin America ( 17 , 26 , 27 ), our findings indicated that CEA was the most prevalent (39.1%, 77/197) study type for full HEE conducted in Brazilian settings between 1980 and 2013. This might be explained by the relative simplicity of the CEA approach compared with CUA that requires developing robust methodology to value health state preferences.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As reported in earlier systematic reviews of HEE studies in Latin America ( 17 , 26 , 27 ), our findings indicated that CEA was the most prevalent (39.1%, 77/197) study type for full HEE conducted in Brazilian settings between 1980 and 2013. This might be explained by the relative simplicity of the CEA approach compared with CUA that requires developing robust methodology to value health state preferences.…”
Section: Discussionsupporting
confidence: 84%
“…This systematic review reveals a steady growing trend in the number of HEE studies being published in the last 6 years (2008–2013). Interestingly, this phenomenon is also observed in Colombia ( 26 ).…”
Section: Discussionmentioning
confidence: 52%
“…Los resultados encontrados denotan la necesidad de avanzar en procesos de adaptación transcultural de los instrumentos que ya existen para evaluar las diferentes áreas de la APS ya que unas de las dificultades del uso internacional de estos instrumentos es la magnitud de los cambios que suelen sufrir cuando son adaptados a diferentes contextos sin atender a recomendaciones sobre este tipo de procesos (22) . Además, a partir de estos resultados, se evidencia que hay dificultades en la estandarización de instrumentos que evalúen la APS, esta misma dificultad ha sido señalada en otro tipo de evaluaciones en el sector salud (23)(24) .…”
Section: Discussionunclassified
“…All costs were expressed in 2015 US dollars (exchange rate of US $1 = 3,149.47 Colombian pesos [COP]). A discount annual rate of 3% for both costs and results was included in the model according to the recommendations from the international literature [31,32].…”
Section: Methodsmentioning
confidence: 99%